2018
DOI: 10.1016/j.fas.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

EFAS Score — Multilingual development and validation of a patient-reported outcome measure (PROM) by the score committee of the European Foot and Ankle Society (EFAS)

Abstract: The multi-language EFAS Score was successfully validated in the orthopaedic ankle and foot surgery patient population, including a wide variety of foot and ankle pathologies. All score versions are freely available at www.efas.co.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…The data were acquired using clinical examination combined with the patients' medical records and standardized 1,[16][17][18][19] In addition to these scores, the ability to return to work and sports, as well as details of any complications or revision surgeries, were recorded. Radiographic analysis was performed by a senior foot and ankle surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…The data were acquired using clinical examination combined with the patients' medical records and standardized 1,[16][17][18][19] In addition to these scores, the ability to return to work and sports, as well as details of any complications or revision surgeries, were recorded. Radiographic analysis was performed by a senior foot and ankle surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that all evaluated instruments were valid and reliable, and none of the foot and ankle specific scales offered advantages when comparing them to lower extremity instruments (the LEFS and the WOMAC). A new PROM called the EFAS score has recently been developed for foot and ankle patients by the score committee of the European Foot and Ankle Society (EFAS) [33]. This new instrument may provide further possibilities is assessing the treatment of foot and ankle diseases as it has been developed to overcome the weaknesses of other foot and ankle specific instruments [33].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the herein used PROMs are not fully validated per the COSMIN group recommendations [2628] and the normative data available for the VAS-FA have not been validated in a foot and ankle trauma population [32]. Future studies should be even more aware of the PROMs chosen and consider scores such as the Self-reported Foot and Ankle Score (SEFAS) [21, 34], Manchester-Oxford foot questionnaire (MOXFQ) [3537].…”
Section: Discussionmentioning
confidence: 99%